Potensi Ekstrak Lengkuas sebagai Fungisida Nabati untuk Mengendalikan Penyakit Karat Daun Anggur (Phakopsora euvitis) - Ani Widiastuti; Reza Fredo Simarmata; Christanti Sumardiyono (Jurnal Fitopatologi Indonesia, 2020)
Potency of Galangal Extract as Botanical Fungicide to Control Grape Leave Rust Disease (Phakopsora euvitis) Grape leaf rust caused by Phakopsora eutivitis is an important disease on grape plants. Botanical pesticide is important to be developed as its application may reduce the usage of synthetic chemical pesticides. This study aimed to determine potency of galangal extract as botanical fungicide against P. euvitis, compared with mancozeb. The methods were galangal extract preparation in evaporated methanol, in vitro toxicity test of galangal extract for LC50 determination, and in planta test using grape seedlings in polybags. LC50 was determined by using SAS JMP Statistical Discovery Program. In planta test was carried out by spraying urediniospore suspension with density of 1 x 106 spores.mL-1, followed by galangal extract or mancozeb spraying at LC90 concentration three days after inoculation. The result showed that galangal extract inhibited spore germination of P. euvitis. LC50 of the galangal extract was 18.33 ppm; LC90 was 53.72 ppm; while mancozeb LC50 was 65.52 ppm and LC90 was 190.71 ppm. In planta experiment showed that galangal extract of 53.72 ppm (LC90) reduced the disease intensity of leaf rust by 16% on the 18th day, while mancozeb of 190.71 ppm (LC90) reduced the disease intensity by 26.4% compared to positive control or untreated-inoculated plants. This study showed that galangal extract is potential to be developed as botanical fungicide to control grape leaf rust disease